Application of Machine Learning Techniques to Tweet Polarity Classification with News Topic Analysis - Park, Hoyeon; Seo, Hyeonjeong; jae Kim, Kyoung; Moon, Gundoo (International Journal of Engineering and Technology, 2018)
The exponential growth of online community provides the tremendous amount of textual information in terms of human behavioral reaction. Thus, online social media platforms such as Twitters, Facebook and YouTube are reflected as an essential part of human relationship networks. Especially, Twitter is widely applied to the disaster situation as a text and it provides critical insights into emergency management. In this study, we propose a topic analysis and sentiment polarity classification with machine learning techniques for emergency management. In this study, we compared the polarity classification models using three machine learning methods and found that the model with random forests showed the best classification performance.